Recent Referees (Journal of Political Economy, 2020)
Previous articleNext article FreeRecent RefereesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreJournal of Political Economy acknowledges the assistance of:Eliot AbramsSumit AgarwalS. Nageeb AliPeter ArcidiaconoCarolina ArteagaJohn AskerSina AtesMiguel BallesterHeski Bar-IsaacBjoern BartlingMarianne BertrandMichael BestChristopher BlattmanAlessandro BonattiKevin BoudreauChristine BraunNick BuchholzKonrad BurchardiSydnee CaldwellJohn CampbellJuan CarrilloLaurent CavenaileChristopher ChambersGary CharnessJames ChoiJay ChoiSteve CicalaChristopher ClappJeffrey ClemensJohn CochraneAlain CohnKimberly CornaggiaVincent CrawfordMichael CunaGordon DahlMelissa DellDavid DemingWill DobbieMatthias DoepkeGregory DowAnna Dreber AlmenbergPiotr DworczakTore EllingsenMax FarrellShuaizhang FengJames FenskeDavid FiglioRaymond FismanJorge Luis GarcíaGreer GosnellDaniel HaanwinckelBruce HansenSamuel HartzmarkEmma HeikenstenTibor HeumannJames HinesRandi HjalmarssonRichard HornbeckErik HurstKoichiro ItoHanan JacobyLaurence JacquetTomas JagelkaPankaj JainCharles JonesPatrick KehoeMaxwell KelloggIgor KopylovDaniel KrahmerTheresa KuchlerGuido KuersteinerMichael KuhnPeter LandryJohn LeahyJustin LeungTim LeunigTeng LiNicola LimodioJo Thori LindAttila LindnerAriel ListoMeng LiuKatrine LokenElena LoutskinaCorinne LowEsfandiar MaasoumiMario MacisGlenn MagermanRobert MargoMarco MariottiAsier MariscalLeslie MarxXavier Mateos-PlanasNiko MatouschekThomas McInishDaniel McMillenHalvor MehlumKonrad MenzelGuy MichaelsStanley MilesJoel MokyrDavid MolitorJack MountjoyKaivan MunshiRebecca MyersonSuresh NaiduSusanne NeckermannNick NetzerTom NicholasJuan NicoliniSam NorrisHessel OosterbeekKevin O’RourkeRobert ÖstlingAmanda PallaisLubos PastorMaria PetrovaA. Mitchell PolinskyMaria PolyakovaThomas QuanDavid RapachDaniel RappoportAlex Rees-JonesA. ReynosoDavid RibarArthur RobsonDaniel RoggerMaya Rossin-SlaterAldo RustichiniLuca SalaAnya SamekFlorian ScheuerFrank SchilbachMolly SchnellCarsten SchroederMoritz SchularickDaniel SchunkHannes SchwandtMichael SchwertPetr SedlacekJesse ShapiroJoseph ShapiroSteven ShavellAndrew ShephardLan ShiRon SiegelOlmo SilvaLuis SimonErik SnowbergGary SolonStefanie StantchevaChristopher StantonJakub SteinerJoel StiebaleBruno StruloviciAlexander TorgovitskyRagnar TorvikBertil TungoddenChristopher UdryCan UrgunWinnie van DijkJohn Van ReenenHans VothReed WalkerChristopher WaltersHongcen WeiCatherine WeinbergerAlexander WhalleyEdward WolffJens WronaNathan YangJunjian YiJiro YoshidaH. YoungBasit ZafarAndy ZapechelnyukOwen ZidarSeth Zimmerman Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 128, Number 4April 2020 Article DOIhttps://doi.org/10.1086/709102 © 2020 by The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.